1973
DOI: 10.1172/jci107447
|View full text |Cite
|
Sign up to set email alerts
|

Renal Bicarbonate Wasting during Phosphate Depletion A POSSIBLE CAUSE OF ALTERED ACID-BASE HOMEOSTASIS IN HYPERPARATHYROIDISM

Abstract: A B S T R A

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
26
2
1

Year Published

1974
1974
1992
1992

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 101 publications
(31 citation statements)
references
References 23 publications
2
26
2
1
Order By: Relevance
“…Hypophosphatemia in our animals was associated with undetectable plasma PTH and normal total and ionized calcium levels (Table I), findings previously described by other investigators (19). An augmented insulin response to a glucose challenge was noted in the hypophosphatemic state ( Fig.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Hypophosphatemia in our animals was associated with undetectable plasma PTH and normal total and ionized calcium levels (Table I), findings previously described by other investigators (19). An augmented insulin response to a glucose challenge was noted in the hypophosphatemic state ( Fig.…”
Section: Discussionsupporting
confidence: 89%
“…For example, LeFevre et al (33) have demonstrated that cell membrane phospholipid is critical in the transport process of all monosaccharides. Recently, phosphate depletion has been shown to lead to intracellular alkalosis (19), which may cause an altered intracellular sodium:potassium ratio produced by the efflux of potassium. By so doing, however, one would expect augmented glucose uptake (34,35).…”
Section: Discussionmentioning
confidence: 99%
“…A decrease in the net tubular reabsorption of magnesium during PD is not surprising because others have reported tubular reabsorptive defects of other substances such as calcium (10), bicarbonate (28), glucose (29), and sodium (30).…”
Section: Discussionmentioning
confidence: 99%
“…Other investigators (28)(29)(30) have attributed the changes in bicarbonate homeostasis in hyperparathyroidism to phosphate depletion induced by PTH rather than to the direct action of the hormone on RHcos.…”
Section: Discussionmentioning
confidence: 99%